EFFECT OF SAWDUST MULCH ON SOIL PROPERTIES AND PERFORMANCE OF Lycopersicum esculentum (TOMATOES) IN AN ALFISOL IN SOUTH WESTERN NIGERIA - ABIODUN, FEMI (Journal of Agricultural Sciences (Belgrade), 2023)
Mulching is an effective method of manipulating crop growing environment to increase yield. A field experiment was carried out at the Teaching and Research Farm of Federal College of Forestry Jericho, Ibadan. The study aimed to examine sawdust mulching effect on selected soil properties, growth and yield of two varieties of tomato. The study was a 4 x 2 factorial experiment laid out in a Randomized Completely Block Design (RCBD) with four replications. Factor one consist of four treatments namely: T0 (Control), T1 (Saw dust mulch (SDM) at 10tonnes/ha), (SDM at 20tonnes/ha) and (SDM at 30tonnes/ha). The second factor is the two varieties of tomato (UC82B and Ibadan local). Plant height, stem girth, number of leaves, branches were collected at 2 weeks interval while the number of fruits, fruit weight (kg/ha) and yield parameters were measured at maturity. These were statistically analyzed using Genstat Statistical Software package and significant means were separated using Least Significant Difference (LSD) at 5% level of significance. Sawdust mulch used has low nitrogen (0.60%) and moderate organic carbon (38.6%). Tomato yield was influenced significantly by sawdust mulch but no significant difference in the variety of tomatoes used. UC82B (117.92kg/ha) at 30t/ha SDM plot had the highest yield, followed by Ibadan local (103.93kg/ha) at 30t/ha SDM plot with Ibadan local (61.94kg/ha) at control plot as least. Tomato with Sawdust mulch at 30t/ha performed best in this study and therefore recommended for farmers in the study area to maximize tomato production.
Keywords: Tomato, Saw dust, Mulching, Soil